Comparison Between Linear Stapler and Circular Stapler After Laparoscopic-Assisted Distal Gastrectomy in Patients With Gastric Cancer - Sun, Danping; Zhang, Renhua; Wei, Meng; Liu, Peng; Zhong, Xin; Liang, Yize; Chen, Yuanyuan; Huang, Yadi; Yu, Wenbin (Frontiers in Surgery, 2022)
Background and Aim: To evaluate the safety and efficacy of laparoscopy distal gastrectomy using linear stapler compared with circular stapler in patients with gastric cancer. Methods: We retrospectively reviewed 173 patients who underwent laparoscopic distal gastrectomy for gastric cancer at a single center from January 2018 to December 2020. Patients were categorized into the linear stapler group and circular stapler group. General data, intraoperative and postoperative outcomes, postoperative pathological results, postoperative complications and postoperative follow-up in the two groups were compared and analyzed. Results: The operation time (208.76±32.92 min vs 226.69±26.92 min，P＜0.05), anastomosis time (71.87±9.50 min vs 90.56±3.18 min，P＜0.05), time to first flatus (68.60±25.96 hours vs 76.16±21.05 hours，P＜0.05), time to first sips of water (3.66±0.61 days vs 4.07±0.77 days，P＜0.05) and time to first liquid diet (4.43±1.02 days vs 5.03±1.70 days, P<0.05) were significantly shorter in the linear stapler group. In addition, the highest postoperative body temperature within 3 days (37.4±0.61 vs 37.7±0.61，P＜0.05) after the operation, white blood cell count (WBC) on the 3rd day (9.07±2.52 vs 10.01±2.98 *10^9/L，P＜0.05) and average gastric tube drainage within 3 days (36.65±24.57 ml vs 52.61±37 ml, P<0.05) were also significantly lower in the linear stapler group. Conclusions: Both circular and linear staplers are safe and feasible for gastrointestinal reconstruction in laparoscopic distal gastrectomy, while linear stapler has advantages over circular stapler in shortening operation time and accelerating postoperative recovery of patients.